The Counter Hegemony of Matriarchy in The Black Family Race - Sechan Rafayan Kharisma (Program Studi Ilmu Komunikasi FISIP UM Buton, 2022)
The phenomenon of the black race in a world that is always depicted as a people who are cornered on the edge by short animated films. Hair Love is an American animated short film written and directed by Matthew A. Cherry. This animated short film was used by Matthew A. Cherry to respond to the discrimination and ugly stereotypes that occur in a black racial family, especially an African-American father. This research was conducted to determine how the counter hegemony matriarchy is depicted in the film Hair Love. The method used in this research is John Fiske's semiotics which is divided into 3 levels, namely; reality level consisting of code appearance, behavior, movement and expression; representation level consisting of camera code and characters; the ideological level found by the counter hegemony ideology against the matriarchy. The approach applied in this research is descriptive qualitative. From the results of this study, it is found that there is a counter hegemony and matriarchal ideology behind this short animated film. The practical matriarchal hegemony counter was launched in the film scene produced by Sony Animation. Show that the rejection of matriarchal domination is created to support black fathers / husbands to educate and nurture their children. Keywords: Cons of Hegemony; Matriarchy; Black Race; Semiotics; Film